Responses of autumn-staging ducks and Coot Fulica atra to the Skjern River Valley wetland restoration project - Bregnballe, Thomas; Clausen, Preben; Fox, Anthony D. (Wildfowl, 2019)
Following 35 years of drainage and intensive arable tillage, the lower Skjern River in west Jutland, Denmark was re-engineered to a meandering riverbed and natural flooding regime to restore sediment and nutrient retention and reduce sedimentation and eutrophication of RingkÃ¸bing Fjord at its efflux. The creation of 22 km2 of lakes, shallow wetlands and seasonally flooded grassland has attracted large numbers of autumn-staging waterbirds, including peaks of 8,800â€“19,700 individuals and more than three-quarters of a million bird-days per annum spent there by nine common freshwater duck species during 2002â€“2016. Over this period, annual numbers of bird-days have declined by 45â€“68% amongst Mallard Anas platyrhynchos, Eurasian WigeonÂ MarecaÂ penelope, Northern Pintail A. acuta and Eurasian Coot Fulica atra, fluctuated without trend for Eurasian Teal A. crecca (hereafter Teal) and Gadwall M. strepera and increased by 99â€“557% amongst Northern Shoveler Spatula clypeata, Common Pochard Aythya ferina (hereafter Pochard), Tufted Duck A. fuligula and Common Goldeneye Bucephala clangula (hereafter Goldeneye). Despite these changes in species composition, there have been no overall declines in total bird-use of the site during 2002â€“2016. Regression models showed a positive relationship between annual numbers of bird-days for Teal and the mean autumn water depth (likely a response to the extent of shallow flooded grassland created by high water levels), as did those for the diving ducks (Pochard, Tufted Duck and Goldeneye), which benefited from the extent and depth of floodwaters. We lament the lack of environmental monitoring post-restoration on the lower Skjern River, which would have provided better information on how changes in food supply, abundance and accessibility affected the annual numbers of autumn-staging waterbirds at the site. Nevertheless, the site, which was formerly devoid of any waterbirds, has immediately become, and remained, one of Denmarkâ€™s five most important freshwater wetlands for autumn-staging waterbirds with minimal management intervention, confirming the considerable potential for such restoration schemes.